A Highly Linear Broadband CMOS LNA Employing Noise and Distortion Cancellation - Wei-Hung Chen; Gang Liu; Zdravko, B.; Niknejad, A.M. (IEEE journal of solid-state circuits, 2008)
A broadband inductorless low-noise amplifier (LNA) design that utilizes simultaneous noise and distortion cancellation is presented. Concurrent cancellation of the intrinsic third-order distortion from individual stages is exhibited with the common-gate and common-source cascade. The LNA is then limited by the second-order interaction between the common source and common gate stages, which is common in all cascade amplifiers. Further removal of this third-order distortion is achieved by incorporating a second-order-distortion-free circuit technique in the common gate stage. Implemented in 0.13 m CMOS technology, this LNA achieved 16 dBm in both the 900 MHz and 2 GHz bands. Measurements demonstrate that the LNA has a minimum internal gain of 14.5 dB, noise figure of 2.6 dB from 800 MHz to 2.1GHz while drawing 11.6 mA from 1.5 V supply voltage.